Social representations of the Brazilian national health care system in the city of Rio de Janeiro, Brazil, according to the structural approach Representaciones sociales del sistema único de salud en el municipio de Río de Janero, Brasil, según el enfoque estructural As representações sociais do sistema único de saúde no município do Rio de Janeiro, Brasil, segundo a abordagem estrutural - Antonio Marcos Tosoli Gomes; Denize Cristina de Oliveira; Celso Pereira de Sá (Universidade de São Paulo, 2008)
The Brazilian National Health Care System The Single Health System (SHS) [SUS-Sistema Único de Saúde] faces difficulties for its effective implementation. This paper aims to characterize the contents and the social representation structure of the Brazilian health care system among health care professionals in the city of Rio de Janeiro. The concept of social memory and the theory of social representation were adopted as frameworks. Five health care institutions were included in this research, with 100 professionals altogether. The free-association technique was used to collect data and the EVOC 2003 software was used analyzed for data analysis. The results signal to a central nucleus, characterized by negative attitudes regarding the SUS. In the contrast area, there is a negative attitude towards the effectiveness of the system and a positive attitude towards the care provided to service users, also showing other principles. At its periphery, the implementation of new opinions about the representation could be observed. It is concluded that the professionals present social representations that recognize the SUS as a new system, eliciting negative attitudes among the professionals, and that is in a process of formation or progressive transformation, raising judgments about the pertinence of the system's principles. El sistema único de salud (SUS) enfrenta dificultades para una efectiva implementación. Este estudio tiene por objetivo caracterizar los contenidos y la estructura de las representaciones profesionales sobre la implementación del SUS en la ciudad de Río de Janeiro. Fueron adoptadas como guías la Teoría de Representación y Memoria Social, desarrolladas en cinco instituciones con cien profesionales. Los datos fueron recolectados a través de narraciones espontáneas y posteriormente analizados por el software EVOC2000. Los resultados muestran un núcleo central que se caracterizan por actitudes negativas frente al SUS. En el área de contraste se observa una actitud negativa que se refiere a la funcionalidad y una positiva, relacionada a la atención de los usuarios. En las zonas periféricas de la ciudad fue observada la incorporación de nuevos posicionamientos frente a la representación. Se concluye que en los profesionales se observan representaciones sociales que reconocen al SUS como un nuevo sistema. Sin embargo, esta incorporación no se da de forma natural, generando críticas sobre la importancia de los principios del sistema. O Sistema Único de Saúde (SUS) enfrenta dificuldades para a sua efetiva implementação. Este estudo objetivou caracterizar os conteúdos e a estrutura das representações dos profissionais acerca da implantação do SUS no município do Rio de Janeiro. Adotou-se como eixos orientadores a Teoria de Representação e de Memória Social, sendo desenvolvido em 5 instituições de saúde, com 100 profissionais. Os dados foram coletados através de evocações livres e analisados pelo software EVOC 2000. Os resultados revelam um núcleo central caracterizado por atitudes negativas frente ao SUS. Na zona de contraste, observa-se atitude negativa referida à funcionalidade e positiva relativa ao atendimento dos usuários. Na periferia, percebe-se a incorporação de novos posicionamentos à representação. Conclui-se que os profissionais apresentam representações sociais que reconhecem o SUS como um novo sistema. No entanto, essa incorporação não vem ocorrendo de forma naturalizada, mas desperta julgamentos sobre a pertinência dos princípios do sistema.